PENGEMBANGAN MEDIA APLIKASI TPW BERBASIS ANDROID UNTUK MENINGKATKAN HASIL BELAJAR TEKNIK DASAR TENIS MEJA DI SEKOLAH DASAR - Tito, Tito Parta Wibowo; Sina, Ibnu; Darmawan, Syamsul; Atqoo, Raden Akhmad (LPPM Universitas Bina Bangsa, 2025)
This study aims to develop and evaluate the effectiveness of an Android-based learning media application for basic table tennis techniques, called TPW. The method used is research and development with the ADDIE model. The research subjects were Year 5 pupils at SD Negeri Ciceri, Serang City. Data analysis techniques included a quantitative approach through learning achievement tests and a qualitative approach through interviews, observations, questionnaires, and documentation. The effectiveness test results showed an improvement in learning outcomes when using the TPW application, with N-gain indices of 0.486 and 0.374 (medium category), which were higher than those achieved with conventional textbooks, which only reached 0.263 and 0.07. Pupils’ mastery learning using the TPW application reached 60%, compared with only 40% when using textbooks. These findings indicate that the TPW application is more effective in enhancing understanding and mastery of basic table tennis techniques. The application can serve as an alternative, interactive, and innovative learning medium in Physical Education (PE) at primary schools, particularly in supporting the development of pupils’ motor skills.